Hybridization Enrichment to Improve Forensic Mitochondrial DNA Analysis of Highly Degraded Human Remains - Young, Jennifer M.; Higgins, Denice; Austin, Jeremy J. (Frontiers in Ecology and Evolution, 2019)
Forensic mitochondrial DNA analysis of degraded human remains using PCR-based Sanger sequencing of the control region can be challenging when endogenous DNA is highly fragmented, damaged and at very low concentration. Hybridization enrichment coupled with massively parallel sequencing (MPS) offers an effective alternative for recovering DNA fragments as small as 30 base pairs (bp) from poorly preserved samples. Here, we apply this methodology on a range of degraded human skeletal remains that have previously been analysed using PCR-based Sanger sequencing with variable success. Our results reaffirm the benefit of targeted enrichment for analysis of degraded remains and highlight the importance of using optimized library preparation and enrichment techniques. We provide an indication of the sequencing depth required to obtain full mtDNA genomes given the complexity of the library and confirm that a second enrichment and/or a very high sequencing effort may be required to obtain full mtDNA genomes for some degraded samples.